Pemberdayaan Keberlanjutan Kewirausahaan Green Product Sabun Eco-Enzyme Varian Calendula, Charcoal, dan Daun Kelor pada Nasyiatul Aisyiyah di Perbatasan Timur Kalimantan Barat - Wulan Purnama Sari; Yeni Yeni; Romi Ferdian; Audra Putri Mahayani; Annisa Triana (Universitas Teuku Umar, 2026)
Due to the low level of entrepreneurial literacy and the poor usage of environmentally friendly local resources among women's organizations in Sintang Regency, this community service project was prompted by the need to improve the situation. Thru the use of green product concepts, this program intends to improve participants' manufacturing capacities, company management skills, and digital marketing abilities. Examples of the tactics that are utilized include hands-on demonstrations, mentorship that encourages participation, and business coaching that is based on digital marketing practices. The findings suggest that there was an improvement in knowledge by 87% and skills by 83%, in addition to the fact that the level of active partner participation in the production system reached 84%. Additionally, the capacity for digital marketing increased by 86%, which is evidence of the efficacy of a practice-based approach. This activity makes a contribution to the development of strategies for environmentally responsible business practices that are based on a circular economy. As a result, the participatory approach has been demonstrated to be effective in enhancing the economic autonomy of communities, particularly among the residents of Nasyiatul Aisyiyah in Sintang Regency.